Excavation of prehistoric roundhouses and post-medieval kilns at Drumyocher and Hospital Shields, Aberdeenshire (Scottish Historical and Archaeological Internet Reports, 2017)
A programme of archaeological watching brief and excavation was carried out by CFA Archaeology Ltd along the route of the Aberdeen to Lochside Natural Gas Pipeline during its construction in 2004. The remains of four truncated Middle Bronze Age roundhouses, one Iron Age post-built roundhouse with a souterrain entered from the house, and two medieval or post-medieval corn-drying kilns were excavated at Drumyocher Farm, near Arbuthnott, Aberdeenshire (NGR: NO 7831 7679). An assemblage of decorated pottery was recovered, unusually for this period. The remains of three truncated probable ring-ditch roundhouses were excavated to the north-east of Hospital Shields Farm, near St Cyrus, Aberdeenshire (NGR: NO 7215 6740); these features have been radiocarbon dated to the Late Bronze Age.